Association of PON1, APOE and SDF-1 Gene Polymorphisms with Treatment Response to Intravitreal Anti-VEGF Treatment in Patients with Retinal Vein Occlusion - Ragkousis,A.; Kazantzis,D.; Georgalas,I.; Theodossiadis, P; Kroupis, C.; Chatziralli, I (Semin.Ophthalmol., 2023)
PURPOSE: The purpose of this study was to determine whether specific genetic polymorphisms affect the response to intravitreal anti-vascular endothelial growth factor (anti-VEGF) treatment in patients with macular oedema secondary to retinal vein occlusion (RVO). METHODS: Participants in this prospective study were 50 patients with macular oedema secondary to RVO, who were treated with intravitreal ranibizumab or aflibercept, and were followed-up for 12 months after initiation of treatment. Five single nucleotide polymorphisms (SNPs) from three different genes (APOE, PON1, SDF-1) were examined as potential predictors for treatment response to intravitreal anti-VEGF agents. RESULTS: Patients with the LL genotype of the PON1 L55M SNP had significantly higher reduction in central subfield thickness (CST) at month 12 after initiation of intravitreal anti-VEGF treatment (101.63 +/- 56.80 mum in LL vs. 72.44 +/- 39.41 mum in LM vs. 40.25 +/- 19.33 mum in MM, p = .026). Patients with the M allele of the PON1 L55M SNP were significantly associated with lower reduction in CST compared to non-carriers (68.29 +/- 38.77 mum in LM + MM vs. 101.63 +/- 56.80 mum in LL, p = .032). CONCLUSION: PON1 L55M SNP may serve as a promising genetic biomarker for predicting response to intravitreal anti-VEGF treatment in patients with macular oedema due to RVO